2018
DOI: 10.1016/j.ejps.2018.08.042
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of human liver membrane transporters: a focus on fetuses and newborn infants

Abstract: Various developmental patterns of protein expression of hepatic transporters emerged in fetuses and newborns up to four months of age. Postmenstrual age was the most robust factor predicting transporter expression in this cohort. Our data fill an important gap in current pediatric transporter ontogeny knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
82
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(88 citation statements)
references
References 39 publications
3
82
1
Order By: Relevance
“… OCT1 : As previously reported, OCT1 mRNA levels in pediatric livers appeared to be comparable to those in adult livers . Nonetheless, OCT1 protein levels have been shown to undergo an age‐dependent increase . This was supported by a recently published clinical study in neonates who were admitted to the neonatal intensive care unit where postmenstrual age as well as OCT1 genotype impacted the PK of the OCT1 substrate morphine .…”
Section: Ontogeny Of Membrane Transporterssupporting
confidence: 68%
See 4 more Smart Citations
“… OCT1 : As previously reported, OCT1 mRNA levels in pediatric livers appeared to be comparable to those in adult livers . Nonetheless, OCT1 protein levels have been shown to undergo an age‐dependent increase . This was supported by a recently published clinical study in neonates who were admitted to the neonatal intensive care unit where postmenstrual age as well as OCT1 genotype impacted the PK of the OCT1 substrate morphine .…”
Section: Ontogeny Of Membrane Transporterssupporting
confidence: 68%
“…In their sample set van Groen et al found that the OATP1B1 expression was significantly higher in the fetal livers compared with that in term neonatal livers. The protein expressions in infants, children, and adults were similar . OATP1B1 is highly polymorphic.…”
Section: Ontogeny Of Membrane Transportersmentioning
confidence: 86%
See 3 more Smart Citations